P - Davis, Christine (Public, 2000)
Patagonia | Jill Yesko Peace | Paul Kelley People | Giorgio Agamben Phantasmagoria | Freda Guttman Photoplay | Susan Lord Poetics | Stephen C. Foster Police Range | Lynne Cohen Political | Andrew James Paterson Popoloid | Laura Calvi Postmodernism | Ken Allan Privacy | Susan Lord Progress | Arnd Jurgensen Provocation | Nada Seferovic Psychoanalysis | Charles Levin